Regiospecificity modification of Geobacillus zalihae T1 lipase via molecular engineering approaches - Albayati, Samah Hashim Khaleel (2022)
To date, only a few lipases have been reported to have sn-1, sn-2, or sn-3- regioselectivity. This single selectivity offers various important applications, especially the most valuable is producing chiral products for the drug and food industries. T1 lipase, which was isolated from Geobacillus zalihae with specific regioselectivity at sn-1,3, was used in this study. This work aims to study the potential of implementing rational and semi-rational protein design methods to target the lid and binding site area of sn-1,3- regiospecific T1 lipase. Three strategies were applied for modifying T1 lipase regiospecificity, and this modification is essential to improve the T1 lipase industrial application, especially in the production of chiral molecules. The first strategy targeted the lid area by a semi-rational protein design method and resulted in 7 variants (F180C, F180G, F180S, F180L, F180I, F180N, and F180Y). The resulting variants showed an increased and decreased in their optimum temperature and thermal denaturation point ranging from 60 to 75 °C, and 63 to 78 °C, respectively, compared to wt-T1, which has an optimum temperature of 70 °C and thermal denaturation point at a temperature of 73 °C. The resulting variants from this strategy have optimum pH as wt-T1 lipase and displayed a modified selectivity toward long-chain pNP-ester (C10-C18) compared to wt-T1 lipase, which has a preference towards C10-C14. All resulting variants displayed different catalytic efficiencies ranging from 309 to 604 ×10-6 s-1 /mM compared to wt- T1 catalytic efficiency of 518.4 ×10-6 s-1 /mM. However, this strategy didn’t show any regioselectivity modification. The second strategy applied was rational design around the binding site, and this approach resulted in only one variant with five (5) mutation sites (1M/F25L/I262V/E189K/V247I). This resulting variant did not show any changes at optimum temperature and pH but enhanced the selectivity toward long-chain pNPester (C14-C18) compared to wt-T1 lipase. The resulting variant showed improved catalytic efficiency around 5472 ×10-6 s-1 /mM compared to wt-T1 lipase but did not result in any regiospecific modifications. The third strategy targeted both the lid by rational design (F180G/F181S) and the oxyanion hole by semi-rational design strategy, which resulted in twelve (12) variants (F16X, X=C, G, V, Y, D, H, S, L, I, W, F, N). The newly generated variants conserved the optimum temperature of 70 ℃. However, thermal denaturation was negatively affected, and this was represented by a decline in the denaturation temperature ranging from 5 to 7 °C. However, these targeted mutations shifted the optimum pH to 10 for some variants compared to pH 9 for wt-T1. Regarding the selectivity study, the resulting variant showed improved selectivity toward pNP-ester long-chain fatty acids from C12-C18 compared to wt-T1 lipase. In addition, the variants of this strategy displayed different catalytic efficiencies, ranging from 86.4 to 777 ×10- 6 s-1 /mM compared to wt-T1 lipase. Furthermore, six variants, F16I, F16V, F16W, F16S, F16G, and F16C, displayed a regioselectivity modification from sn-1,3 regioselectivity of wt-T1 to only sn-3. Gas- chromatography (GC) with flame ionization detection of these six variants confirmed the regioselectivity modification. The modified regiospecific variants were shown to have a varied preference toward different palm stearin fatty acids lengths ranging from C16 to C20:1 compared to wt-T1 lipase with the specificity of C16 to C18:1. The sn-3 modified regiospecific structure (F16W) and wt- T1 lipase structures were remodelled and predicted within open conformation, then subjected to docking and molecular simulation (MD) study complexed with an acylglycerol analogue as a substrate. The docking study showed that sn-3 modified regiospecific structure has a higher affinity toward sn-3 acylglycerol chain than wt-T1, which displayed binding affinity toward sn-1,3 acylglycerol chain. Whereas the MD simulation study showed conformational changes that occurred were approximately on the lid domain and distant from the oxyanion hole mutation site (Zn2+ coordination domain), consisting of helices α3 and α5. The conformational changes resulting from altering bulky side-chain residues of the lid and oxyanion hole have increased binding site flexibility and affected the hydrogen networking of the Zn2+ coordination domain. In conclusion, the substitution of lid and oxyanion hole residues (strategy three) successfully modified regioselectivity and shifted lipase specificity and activity. Therefore, targeting both the lid and binding site (strategy three) is sufficient to create a novel regiospecificity of an enzyme. Thus, sn-3 lipase is essential in producing pure fatty acids with high specificity, which can be applied to obtain high-value chemicals for drug and food industries.